A Delphi-based study on the innovation practices in the Albanian financial sector. (15th January 2020) - Çipi, Amali; Pulaj, Enida
Based on an application of the Delphi technique, this paper aims to analyse the current situation of innovation practices in Albania, based on an application of the Delphi technique to a panel of Albanian financial institutions executives. Despite the short life of most of the financial companies in the Albanian trade market, results show that executives have a relatively good level of knowledge regarding the benefits of the innovation approach to the firm, but there is a lack of some innovation types used by their companies. Furthermore, there is a low level of investment amount to be spent in innovation, indicating a non-possibility to create new products or processes and thus not having the possibility to be a leader and create better promise for the company growth. Government is advised to consider innovation as a mediating factor to achieve better business performance and thus helping and promoting sustainable macroeconomic growth.